The Construction and Immunogenicity Analyses of Recombinant Pseudorabies Virus With NADC30-Like Porcine Reproductive and Respiratory Syndrome Virus-Like Particles Co-expression - Zhao, Jun; Zhu, Ling; Xu, Lei; Li, Fengqing; Deng, Huidan; Huang, Yao; Gu, Sirui; Sun, Xianggang; Zhou, Yuancheng; Xu, Zhiwen (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome (PRRS) and pseudorabies (PR) are highly infectious and economically significant swine diseases in China. Respiratory system and reproductive system are their main target systems. Previous studies showed that the existing PRV and PRRSV commercial vaccines could not provide complete protection against PRV variant strains and NADC30-like PRRSV strains in China. In this study, the PRV variant strain XJ and NADC30-like PRRSV strain CHSCDJY-2019 are used as the parent for constructing a recombinant pseudorabies virus rPRV-NC56 with gE/gI/TK gene deletion and co-expressing NADC30-like PRRSV GP5 and M protein. The rPRV-NC56 proliferated stably in BHK-21 cells, and it could stably express GP5 and M protein. Due to the introduction of the self cleaving 2A peptide, GP5 and M protein were able to independently express, and they were able to form virus like particles (VLPs) of PRRSV in rPRV-NC56 infected BHK-21 cells. The rPRV-NC56 is safe for use in mice, and can colonize and express the target protein in mouse lungs for a long time. The vaccination with rPRV-NC56 induces PRV and NADC30-like PRRSV specific humoral and cellular immune responses in mice, and protects 100% of mice from virulent PRV XJ strain. Further, the virus neutralizing antibody (VNA) elicited by rPRV-NC56 showed significantly lower titer against SCNJ-2016 (HP-PRRSV) than against CHSCDJY-2019 (NADC30-like PRRSV). Thus, rPRV-NC56 appears to be a promising candidate vaccine against NADC30-like PRRSV and PRV for the control and eradication of the variant PRV and NADC30-like PRRSV.